Nanoscale architecture of (La0.6Sr1.4)0.95Mn0.9B0.1O4 (BCo, Ni, Cu) Ruddlesden–Popper oxides as efficient and durable catalysts for symmetrical solid oxide fuel cells. (September 2020) - Wang, Junkai; Zhou, Jun; Yang, Jiaming; Zong, Zheng; Fu, Lei; Lian, Zhongjie; Zhang, Xinchang; Wang, Xuan; Chen, Chengxiang; Ma, Wanli; Wu, Kai
Abstract: A-site deficient (La0.6 Sr1.4 )0.95 Mn1-x Bx O4 (x = 0, 0.1, B= Co, Ni, Cu) (LSMBO4 ) Ruddlesden–Popper oxides were demonstrated as promising symmetrical electrodes for Sc2 O3 stabilized ZrO2 (SSZ) electrolyte supported solid oxide fuel cells (SOFCs). The formation of oxygen vacancies is facilitated with the B-site transition metal doping. A-site defect promotes the exsolution of catalytic Co, Ni or Cu nanoparticles on the surface of materials in reducing atmosphere. The electrochemical performances in air and reducing atmosphere are significantly optimized via the substitution of Mn by Co, Ni or Cu and exsolved metallic nanoparticle catalysts. Especially, the materials doped by B-site with Cu shows the highest electrical conductivity of 37.54 S cm −1 and 6.82 S cm −1 and lowest polarization resistance of 0.12 Ω cm 2 and 0.32 Ω cm 2 at 750 °C in air and 5% H2 /N2, respectively. The maximum power density of 623.1 mW cm −2 at 750 °C is achieved for an electrolyte-supported symmetrical single cell with the LSMBO4 -SSZ composite electrode operating with pure H2 . All these results indicate that LSMBO4 can be promising candidates for symmetric electrodes of SOFCs. Graphical abstract: Image 1 Highlights: Co, Ni, Cu exsolved as uniformly distributed metallic nanoparticles after reduction. The low Rp of 0.12 Ω cm 2 in air and 0.32 Ω cm 2 in 5%H2 /N2 were achieved at 750 °C with the LSMCuO4 -SSZ composite electrode. The symmetrical cells represent a maximum power density of 623.1 mW cm −2 at 750 °C under pure H2 with the LSMCuO4 -SSZ composite electrode.